Perlindungan Konsumen Atas Penyebaran Berita Bohong Melalui Transaksi Elektronik Yang Mengakibatkan Kerugian Konsumen - Elfrida Ratnawati; Faruqy Nailufar; Rosdiana Rosdiana (Fakultas Hukum Universitas Balikpapan, 2023)
Guidelines for implementing consumer understanding in Article 28 paragraph (1) of Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions (UU ITE) which provide boundaries and scope of application, which were originally very broad and in general becomes narrower and specific where the definition of consumer in Law Number 8 of 1999 concerning Consumer Protection is only specifically for Final Consumers as in the Joint Decree (SKB) of the Minister of Communication and Information, the Attorney General of the Republic of Indonesia and the Chief of Police Number 229 of 2021, Number 154 of 2021 and Number KB/2/VI/2021 which provides guidelines for implementing the definition of the word